My hero academia. Vol. 1, Izuku Midoriya: origin - Horikoshi, Kohei, 1986-; Cook, Caleb D. (Shonen Jump manga., 2015)
In a world where eighty percent of the population is born with "quirks" which give them superpowers, and battles between heroes and villains are an everyday occurrence, the twenty percent born without quirks are simply "quirkless." Quirkless fourteen-year-old Izuku Midoriya wishes he had a power, and when he meets All Might, the greatest hero in the world, his life changes forever.